HUBUNGAN POLA ASUH DENGAN POLA PERKEMBANGAN SEKSUAL SEKUNDER PADA SISWA SMP - Mayang Sari, Uci; Musvita Ayu, Suci (MEDIA ILMU KESEHATAN, 2016)
Background: Adolescence is a transition period from childhood to adulthood, both physically and psychologically. Parents are generally considered as primary teachers for their children, therefore parents play important roles in children development. Parenting style is one of the factors associated with the pattern of secondary sexual development. Objective: This study aimed to examine the relationship between parenting style and the pattern of secondary sexual development in junior high school students. Methods: This research was an observational analytic study, using cross sectional approach. The study population was all male students at SMP 1 Berbah Yogyakarta (188 students). Samples were selected using purposive sampling, involving 143 respondents. Data were analyzed with Chi square test. Result: There was a correlation between parenting style and the pattern of secondary sexual development (p= 0.000 <0.05), with PR value of 4,975, CI 95 % of 1,831-13,516. Conclusion: There was a relationship between parenting style and the pattern of secondary sexual development in junior high school students. Keywords: Adolescence, Parenting, Patterns of Sexual Secondary Students